Community Aging Initiatives and Social Capital: Developing Theories of Change in the Context of NORC Supportive Service Programs. (March 2014) - Greenfield, Emily A.
This study aimed to develop theory on how Naturally Occurring Retirement Communities (NORC) Supportive Service Programs potentially transform social relationships within communities to promote aging in place. Data were analyzed from semi-structured in-depth interviews with 10 lead agencies representing 15 NORC programs in New Jersey. Results indicated that professionals seek to infuse capital within three domains of relationships: lead agency staff's relationships with older adults, formal service providers' relationships with each other, and older adults' relationships with each other. This social capital potentially enhances the amount of community-based services and supports within a residential area, as well as their accessibility, appropriateness, responsiveness, and coherence.